1989
DOI: 10.1016/0014-5793(89)81639-4
|View full text |Cite
|
Sign up to set email alerts
|

Suramin, an anti‐cancer drug, inhibits protein kinase C and induces differentiation in neuroblastoma cell clone NB2A

Abstract: Protein kinase C purified from rat brain was found to be inhibited by suramin, a substance used originally in the therapy of antitrypanosomic infections and more recently proposed as antineoplastic agent. The inhibition of suramin was competitive with one of the substrates of the enzyme, ATP with a K, of 10 PM. At concentrations adequate to inhibit the isolated enzyme, suramin was shown to slow the rate of proliferation of neuroblastoma NB2A cells in vitro and to induce their differentiation as evidenced by ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 14 publications
0
42
1
Order By: Relevance
“…These include, in the context of antiproliferation, inhibition of key enzymes involved in the intracellular transduction of mitogenic signals, e.g. phosphoinositol and diacylglycerol kinases (Kopp & Pfeiffer, 1990), protein kinase C (Hensey et al, 1989), DNA polymerases (Spigelman et al, 1987) and topoisomerase II (Bojanowski et al, 1992). Suramin has also been shown to disrupt the coupling of G-proteins to receptors (Butler et al, 1988).…”
mentioning
confidence: 99%
“…These include, in the context of antiproliferation, inhibition of key enzymes involved in the intracellular transduction of mitogenic signals, e.g. phosphoinositol and diacylglycerol kinases (Kopp & Pfeiffer, 1990), protein kinase C (Hensey et al, 1989), DNA polymerases (Spigelman et al, 1987) and topoisomerase II (Bojanowski et al, 1992). Suramin has also been shown to disrupt the coupling of G-proteins to receptors (Butler et al, 1988).…”
mentioning
confidence: 99%
“…Staurosporine, though first reported to be the most potent inhibitor of PKC [7], was also found to inhibit various protein kinases at a certain range of concentrations [17] and induce cell differentiation in some types of cells [18][19][20]. The concentration of staurosporine used in the present study seems to be suitable for the potentiation of PKC to differentiate the 3T3-LI cells [7,21].…”
Section: Discussionmentioning
confidence: 67%
“…The present study suggested that inhibition rather than activation of PKC appears to be associated with differentiation of 3T3-L1 cells. There are also some reports that other PKC inhibitors enhanced differentiation in neuroblastoma cells [18,19] and HL-60 cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…To extend our study to structurally distinct potential kinase inhibitors not contained in the Fine Chemicals Directory used, we tested suramin, a compound previously shown to inhibit protein kinase C 39 and, very weakly, cAPK 40 . Suramin was docked into the GRK2 model and attained a high GRK2 score with a favorable fit into the central cleft ( Figure 2C [static image]), in preference to cAPK.…”
Section: Aaps Pharmscimentioning
confidence: 99%